2022
DOI: 10.3389/fpubh.2022.838579
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Current State of Awareness, Knowledge, and Attitudes Toward Breast Cancer? A Cross-Sectional Survey Among Health and Non-health College Students

Abstract: ObjectiveTo document breast cancer (BC) knowledge, awareness, and attitudes among female undergraduate students studying at health and non-health colleges.MethodsA 3-month cross-sectional study was conducted among female undergraduate students studying at health and non-health subject colleges affiliated to a public university. Convenience sampling was employed, and a previously validated questionnaire available in English and Arabic languages was used. Multiple linear regression was used to report the predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The three most recognized symptoms of breast cancer, as reported by our respondents, are breast lump, nipple changes, itching in the breast, and changes in breast size and shape. This is in line with two previous studies [ 11 , 13 ]. However, a large proportion of our sample didn’t recognize nipple secretions, breast pain, and soreness as symptoms of breast cancer.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The three most recognized symptoms of breast cancer, as reported by our respondents, are breast lump, nipple changes, itching in the breast, and changes in breast size and shape. This is in line with two previous studies [ 11 , 13 ]. However, a large proportion of our sample didn’t recognize nipple secretions, breast pain, and soreness as symptoms of breast cancer.…”
Section: Discussionsupporting
confidence: 94%
“…But, most of them don’t practice BSE [ 12 ]. Lastly, a study conducted among 506 female undergraduate students demonstrated an acceptable level of knowledge [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…population of 425300. Study sample size was calculated after adjusting potential nonresponse rate using below formula as described in various studies [ 13 15 ], where n is “required sample size”, N is “total population size”, d is “error margin” (usually 0.05 is an ideal value when “confidence interval/level” is at 95%, n n is “sample size (after consigning nonresponse rate”, n is “earlier calculated sample size”, and d is “nonresponse rate”. After the above calculation, the final sample estimated for this study was 460 whereby we managed to obtain 533.…”
Section: Methodsmentioning
confidence: 99%
“…population of 425300. Study sample size was calculated after adjusting potential nonresponse rate using below formula as described in various studies [13][14][15],…”
Section: Sample Sizementioning
confidence: 99%
“…Therefore, it requires concerted efforts to address the knowledge debacle. Considering the example of universities in Saudi Arabia to increase awareness of women specific disease such as breast cancer [ 25 ], universities in Pakistan can follow suit and observe a month of awareness of PCOS, conduct awareness campaigns during this time, distribute educational materials and pamphlets, merchandize with awareness logo and signage, etc., and arrange talks or seminars for their students with renowned professionals having substantial contribution in this field.…”
Section: Discussionmentioning
confidence: 99%